EXPLORING EFL UNDERGRADUATE STUDENTS’ INSIGHT TOWARD ONLINE ENGLISH LEARNING QUALITY DURING COVID-19 PANDEMIC - Dinda Ismu Asyifa (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2021)
COVID-19 disease has hit many countries since 2020. In this pandemic era, every field must getting used to technology things, such as online learning and teaching activities. Even though the educational field is facing the pandemic, it does not mean the quality of teaching and learning is not upgraded. This study aimed to find EFL undergraduate students’ insight toward the quality of online English learning during COVID-19 pandemic. There were 60 participants from this study, 30 from English major and 30 from non-English major. This study used quantitative method by applying survey design. However, government, institutions, and lecturers must work together to keep and increase the quality of online English learning.